Pengaruh Dividen, Profitabilitas Dan Solvabilitas Terhadap Nilai Perusahaan : Studi Kasus Pada Perusahaan Food And Beverages Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2021 - Usi Sulistiana; Elan Eriswanto (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to determine the effect of dividends, profitability and solvency on firm value in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Dividends are measured using the dividend payout ratio (DPR), profitability is measured using return on assets(ROA) and solvency is measured using the debt to equity ratio (DER) and company value is measured using price to book value (PBV). This type of research is quantitative research, sampling in this study was carried out by purposive sampling method with predetermined criteria resulting in a sample of 16 companies. The analytical method used is multiple linear regression analysis using SPSS version 25. The partial results show that dividends and solvency have no effect on firm value, while profitability has a significant effect on firm value, simultaneous or simultaneous test results show that the independen variables namely dividends, profitability and solvency have a significant effect on firm value.